Controlled variable oxidative doping of individual organometallic nanoparticles - Feng, A; Cheng, W; Holter, J; Young, N; Compton, R (Wiley, 2016)
The charging and controlled oxidative doping of single organometallic ferrocene nanoparticles is reported in aqueous sodium tetrafluoroborate using the nano‐impacts method. It is shown that ferrocene nanoparticles of approximately 105 nm diameter are essentially quantitatively oxidatively doped with the uptake of one tetrafluoroborate anion per ferrocene molecule at suitably high overpotentials. By using lower potentials, it is possible to achieve low doping levels of single nanoparticles in a controlled manner.